E. coli Group 1 Capsular Polysaccharide Exportation Nanomachinary as a Plausible Antivirulence Target in the Perspective of Emerging Antimicrobial Resistance - Sachdeva, Shivangi; Palur, Raghuvamsi V.; Sudhakar, Karpagam U.; Rathinavelan, Thenmalarchelvi (Frontiers in Microbiology, 2017)
Bacteria evolving resistance against the action of multiple drugs and its ability to disseminate the multidrug resistance trait(s) across various strains of the same bacteria or different bacterial species impose serious threat to public health. Evolution of such multidrug resistance is due to the fact that, most of the antibiotics target bacterial survival mechanisms which exert selective pressure on the bacteria and aids it to escape from the action of antibiotics. Nonetheless, targeting bacterial virulence strategies such as bacterial surface associated polysaccharides biosynthesis and their surface accumulation mechanisms may be an attractive strategy, as they impose less selective pressure on the bacteria. Capsular polysaccharide (CPS) or K antigen that is located on the bacterial surface armors bacteria from host immune response. Thus, unencapsulating bacteria would be a good strategy for drug design, besides CPS itself being a good vaccine target, by interfering with CPS biosynthesis and surface assembly pathway. Gram-negative Escherichia coli uses Wzy-polymerase dependent (Group 1 and 4) and ATP dependent (Group 1 and 3) pathways for CPS production. Considering E. coli as a case in point, this review explains the structure and functional roles of proteins involved in Group 1 Wzy dependent CPS biosynthesis, surface expression and anchorage in relevance to drug and vaccine developments.